Raising Climate Change Awareness Through Community Environmental Education: A Case Study Of “One World, One Goal” Project - Baras, Andrés; Maddi, Maddi (Global Education Journal, 2024)
Given the increasing importance of environmental awareness, it is now widely acknowledged that environmental education should be introduced and ingrained from a young age, both in formal educational settings and within the family environment (non-formal education). The present case study examines the implementation and outcomes of a pioneering project, "One World, One Goal: Connecting for Climate Action," carried out in partnership with the prestigious organisation "Ngeteh Sore." This project goes beyond geographical limits to bring together communities from around the world with a common dedication to environmental stewardship. The project aims to empower individuals, especially parents in Indonesia, by organising carefully selected online talks. These discussions provide them with the necessary knowledge, resources, and inspiration to effectively address the challenges posed by climate change. The project facilitates a worldwide conversation on urgent environmental concerns, such as water scarcity, pollution, green growth, and sustainability, by assembling a varied group of knowledgeable speakers from nine nations. The programme employs a novel approach to not only distribute crucial information but also stimulate concrete action at the local level. The project acts as a catalyst for transformative change by encouraging participants to engage in thought-provoking discussions, share insights, and commit to collective action. It aims to create a more sustainable and resilient future for future generations, with a specific focus on improving educational wellbeing and promoting cross-cultural studies.